1983
DOI: 10.1007/bf01258154
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctions and septate-like junctions between neurons of the opisthobranch molluscNavanax inermis

Abstract: The buccal ganglia of Navanax inermis were studied by thin section, lanthanum infiltration and freeze fracture. Freeze fracture clearly demonstrates small gap junctions between neuronal processes in the neuropil, many of which are known to be electrotonically coupled. Junctional particles cleave with the P-face. In thin section, gap junctions appeared as small blurred contacts, presumably because of the small size of the junctions. Lanthanum infiltration was poor and failed to aid in identifying gap junctions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
3
5
0
Order By: Relevance
“…The dramatic change in strength of coupling associated with these two patterns of firing is attributable to shunting of intercellular current by activation of inhibitory chemical synapses (110). Although a change in resistance of the junctional membrane has not been totally ruled out, the morphological localization of chemical synapses near the site of coupling and the changes in input and transfer resistances recorded in the two states are consistent with uncoupling due solely to changes in nonjunctional resistances (54,110). This sort of uncoupling may also occur in the inferior olive in the mammalian CNS (109).…”
Section: Introduction To Physiological Studies Of Couplingsupporting
confidence: 52%
“…The dramatic change in strength of coupling associated with these two patterns of firing is attributable to shunting of intercellular current by activation of inhibitory chemical synapses (110). Although a change in resistance of the junctional membrane has not been totally ruled out, the morphological localization of chemical synapses near the site of coupling and the changes in input and transfer resistances recorded in the two states are consistent with uncoupling due solely to changes in nonjunctional resistances (54,110). This sort of uncoupling may also occur in the inferior olive in the mammalian CNS (109).…”
Section: Introduction To Physiological Studies Of Couplingsupporting
confidence: 52%
“…Because the coupling between the cells of Portunus is large (Tazaki & Cooke, 1979a), it could be argued that the small size of the appositions makes them unlikely candidates for these electrical synapses; however, this argument has no validity. As shown by Hall et al (1983), small, scattered clusters of intercellular channels can account for large electrical coupling, provided that they are present in sufficient numbers.…”
Section: Electrical Junctions Between Large Cellsmentioning
confidence: 98%
“…If the coupling between the large cells occurs primarily through a diffuse network of small junctions sited on the fine terminal arborizations of their collaterals, as suggested by our data, their low-pass filtering characteristics could be readily explained (Bennett, 1966), since these processes, being located at some distance from the zone of spike initiation, interpose a load capacitance between the site of intercellular current spread and that of the excitable membrane. It is interesting to note that the junctions between the giant neurons of Navanax, which are ruade up by numerous but small patches of intercellular channels (Hall et al, 1983) between fine neuronal processes, also act as a low-pass filter (Levitan et al 1970).…”
Section: Electrical Junctions Between Large Cellsmentioning
confidence: 99%
“…In addition, through the use of HRP labelling, this is the first report of gap junctions connecting the axon collaterals of two identified molluscan neurons (R19, L19) which are known to be electrically coupled (Bulloch, 1985b). Previous ultrastructural studies of molluscan ganglia found it difficult to identify unambiguously gap junctions in thin sections and have relied primarily on freeze fracture (Hall et al, 1983(Hall et al, , 1984Kaczmarek et al, 1979;Roubos et al, 1985). The use of hypertonic fixatives, en bloc uranyl acetate, and a goniometer tilting stage in this study, however, were found greatly to facilitate the detection of gap junctions in thin plastic sections.…”
Section: Gap Junctionsmentioning
confidence: 70%